2016
DOI: 10.3390/jdb4010002
|View full text |Cite
|
Sign up to set email alerts
|

Hermes (Rbpms) is a Critical Component of RNP Complexes that Sequester Germline RNAs during Oogenesis

Abstract: The germ cell lineage in Xenopus is specified by the inheritance of germ plasm that assembles within the mitochondrial cloud or Balbiani body in stage I oocytes. Specific RNAs, such as nanos1, localize to the germ plasm. nanos1 has the essential germline function of blocking somatic gene expression and thus preventing Primordial Germ Cell (PGC) loss and sterility. Hermes/Rbpms protein and nanos RNA co-localize within germinal granules, diagnostic electron dense particles found within the germ plasm. Previous w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 66 publications
2
25
0
Order By: Relevance
“…Fu et al, 2015). In vitro assays suggested that the C-terminal region increases RNA binding affinity and possibly the oligomeric state of RBPMSA (Farazi et al, 2014) and the C-terminal 34 amino acids of Xenopus RBPMS2 is 505 required for binding to Nanos1 RNA in vivo (Aguero et al, 2016). In preliminary studies we have also found the C-terminal region to be essential for splicing regulation (data not shown).…”
Section: Activity Of Rbpms Isoformsmentioning
confidence: 54%
“…Fu et al, 2015). In vitro assays suggested that the C-terminal region increases RNA binding affinity and possibly the oligomeric state of RBPMSA (Farazi et al, 2014) and the C-terminal 34 amino acids of Xenopus RBPMS2 is 505 required for binding to Nanos1 RNA in vivo (Aguero et al, 2016). In preliminary studies we have also found the C-terminal region to be essential for splicing regulation (data not shown).…”
Section: Activity Of Rbpms Isoformsmentioning
confidence: 54%
“…It is degraded at oocyte maturation, while overexpression accelerates oocyte maturation ( Song et al, 2007 ). RBPMS has also been shown to interact with the germline associated protein Nanos to sequester it to germinal granules destined for the germ cell lineage ( Aguero et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…The significance of these differences in Velo1 behavior are not clear, but it has been known for some time, based on ultrastructural and mRNA localization studies, that germ plasm assembles in a specific vegetal subregion of the Balbiani body (Kloc and Etkin 1995; Kloc et al 2002b). Thus, the formation of bona fide germ plasm may involve different structural forms of Velo1, likely in addition to specific protein-protein interactions and the formation of germ plasm RNP granules [i.e., see (Nijjar and Woodland 2013a; Aguero et al 2016)]. These mechanisms will be briefly reviewed in the following section.…”
Section: The Origin Of Animal-vegetal Polarity During Oogenesismentioning
confidence: 99%
“…One of these requisite oocyte proteins could be Rbm42b (see above). Recent data show that Rbpms2 can bind nanos1 in the germinal vesicle and can also interact with Ptbp1 ( alias hnRNPI), likely also in the GV (Aguero et al 2016). Ptbp1 has been implicated in nuclear RNP formation and remodeling in the context of gdf1 localization (Lewis et al 2008).…”
Section: Rna Localization Mechanismsmentioning
confidence: 99%